Heritage Transformation and Resignification of Vernacular Housing in a Native Peruvian Community (Islas, 2025)
Introduction: This research examines the vernacular housing of El Wayku native community in Lamas, with the aim of analyzing the process of transformation and resignification of the heritage values attributed to it in a native community of Peru.Method: This study follows a mixed-methods approach, starting with the definition of the object and area of study, as well as the internal and external subjects involved. According to its scope, it is a descriptive–cross-sectional–explanatory study. Data collection involved bibliographic information from previous studies, triangulated through direct observation of the study area (photographic recording forms and planimetries), and the conduction of structured interviews.Results: Through the comparison of documentary sources and fieldwork, a significant transformation process of the rammed earth vernacular housing was evident within the study area. The interviews revealed a generally positive perception among the subjects regarding the heritage values of form, use, and symbolism, with distinctive assessments in each case that point to a resignification of the object of study.Conclusion: Regarding the resignification process, it was found that for some heritage subjects, the rammed earth vernacular houses lack certain specified values; however, these dwellings can become heritage and, in doing so, stand out in the Amazon region as a particular model.
Keywords: vernacular housing; rammed earth housing; cultural heritage; cultural identity; heritage resignification